Financial Analysis of the Sweet Bread Business (Case Study: Shinta Bakery Sweet Bread Business in Sarimulya Village Rimbo Ilir District Tebo Regency) - Asminar Asminar; Fajar Dedy Kuswanto; Asnawati Is Asnawati Is (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2024)
Bread, lovely bread with various fillings and plain bread, is a popular food consumed by all ages, from toddlers to adults. This research aims to calculate the income of the Shinta Bakery Sweet Bread Business in Sarimulya Village, Rimbo Ilir District, Tebo Regency, and to analyze the financial aspects of the business. The research location was chosen purposively in Sarimulya Village, the only sweet bread provider in the area. The research used the case study method from December 25, 2019, to January 25, 2020. Data was analyzed quantitatively descriptively, with a focus on income analysis models and financial analysis. Analysis tools include a project analysis approach with calculations of Net Present Value (NPV), Internal Rate of Return (IRR), and Net Benefit-Cost Ratio (Net B/C Ratio). The research results show that the annual income of the Shinta Bakery Sweet Bread Business is IDR 171,788,600, with financial analysis showing a positive NPV at a loan interest rate of 10%, an IRR that is greater than the loan interest rate, and a Net B/C Ratio that is greater than one, indicating that this business is worthy of further development.